Behavioural Biases in Impact Investing Empirical Analysis - Aluru, Sumera; Tej , BVR Vishnu (Electronic Journal of Business and Management, 2023)
Impact Investing has gained impetus from both investors and financial institutions owing to its dynamism for global sustainability and the financial landscape. Approaches to investing are evolving to incorporate environmental, social, and governance (ESG) aspects, indicating an emergent need for investments that are in line with individual values and ethical convictions. This study aims to provide empirical evidence for the Monday and January returns puzzle in socially responsible stocks while exploring behavioural biases while taking impacting investing decisions. Historical prices for six impact stocks from different sectors for a period of six years (2018–2023) were analysed to identify the existence of Monday returns and January returns puzzle for all the stocks considered. The standard deviation analysis and covariance analysis of daily returns vs. Monday returns alongside average monthly returns vs. January returns reveals there is a substantial difference, while ANOVA Test results validate the above results and provide evidence for the puzzle. Primary data was collected from 173 retail investors from Bangalore city to find that 24.3% are emotional in investing and (43.9%) opine emotions play a moderate role. Investors (56.6%) agreed that brisk market trends affect their emotions. A sense of fulfilment (38.2%), societal concern (35.3%), and higher self-esteem (32.4%) are the emotional drivers for impact investing. The over-confidence tendency about impact investing was expressed by (58.3%), while the mental accounting tendency by (63.8%). Investors tend to be more overconfident about impact investing in contrast to their normal investment abilities, while they also tend to exhibit a high framing effect while assessing their investment skills in general and impact investing skills in particular.